Phytochemical Constituents Isolated from the Stem Bark of Bauhinia monandra - Ferrari,Jailton (2019)
ABSTRACT The methanolic extract from stem bark of Bauhinia monandra, a medicinal plant employed in folk medicine, yielded by column chromatography lup-20(29)-en-3β,24-diol ( 1) and methyl galloate (2) along with β-sitosterol ( 3). These known phytoconstituents are being reported for the first time from this plant and their structures were established by NMR and MS spectral studies and by comparison with their literature data. Furthermore, lup-20(29)-en-3β,24-diol (1 ), a minor constituent, was isolated from this genus for the first time.